Periodontal Treatment Needs of Smokers in Comparison to Non-Smokers: A Comparative Study - Nida Ayub, Khalfan Haider, Laiba Amer, Asma Shakoor, Salman Aziz, Rabeea Yaqoob, Hira Butt, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the periodontal treatment needs of smokers in comparison to non-smokers. Methodology: A Cross sectional comparative study was carried out on 100 patients, 50 smokers and 50 non-smokers, visiting Sharif Medical and Dental College, Lahore from June 2019 to July 2020. Intra-oral examination was done using the Community Periodontal Index of Treatment Needs (CPITN). Recorded data was coded, entered and analyzed using SPSS statistical Package version 23. Results: Majority of the smokers and non-smokers (100%) required oral hygiene instructions and had periodontal treatment needs (TN1). It was seen that a higher percentage of smokers (92%) required Scaling and prophylaxis and Oral hygiene instructions (TN 2) in comparison to non-smokers (36%). It was seen that 26 % smokers and none of the non-smokers required required complex treatment, scaling, prophylaxis and oral hygiene instructions (TN3). Conclusion: Majority of the smokers and non-smoke required oral hygiene instructions and had periodontal treatment needs (TN1). A higher percentage of smokers required Scaling and prophylaxis and Oral hygiene instructions (TN 2) as well as complex treatment, scaling, prophylaxis and oral hygiene instructions (TN3) in comparison to non-smokers Keywords: Periodontal treatment needs, smokers, non-smokers, Community periodontal index of treatment needs (CPITN).